2021
DOI: 10.1037/adb0000738
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned versus planned simultaneous alcohol and marijuana use in relation to substance use and consequences: Results from a longitudinal daily study.

Abstract: Objective: The current study expands the literature on simultaneous alcohol and marijuana (SAM) use by focusing on the distinction between unplanned and planned SAM use to identify potential intervention targets. This study explored whether unplanned or planned SAM use was associated with differences in alcohol and/or marijuana use and consequences. Method: A community sample of young adults (aged 18-25) with recent alcohol and SAM use was recruited [N = 409; mean (SD) = 21.61 (2.17) years; 50.9% female; 48.2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 37 publications
7
29
0
Order By: Relevance
“… 45 Still, not all papers found a link between same-day co-use and consequences after controlling for alcohol and/or marijuana use. 29 , 32 , 67 , 75 For example, among college men, there was no evidence of same-day co-use increasing the likelihood of interpersonal conflict above and beyond alcohol or marijuana use. 67 …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“… 45 Still, not all papers found a link between same-day co-use and consequences after controlling for alcohol and/or marijuana use. 29 , 32 , 67 , 75 For example, among college men, there was no evidence of same-day co-use increasing the likelihood of interpersonal conflict above and beyond alcohol or marijuana use. 67 …”
Section: Resultsmentioning
confidence: 97%
“… 15 , 23 28 One paper also found that males consumed greater amounts of alcohol and were high for greater lengths of time on SAM use days than females. 29 Fewer papers examined race/ethnicity differences. Those that did generally found that White young adults, in comparison to young adults of other racial/ethnic groups, were more likely to engage in SAM use, did so more frequently, and tended to consume greater quantities of alcohol and marijuana when engaging in SAM use.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, we hypothesized that engaging in simultaneous use at a party, at a friend's place, with friends, with more intoxicated people, and with more people using cannabis would be associated with planned simultaneous use, whereas using at home or alone would be related to unplanned simultaneous use. Consistent with Fairlie et al (2021), we hypothesized that planned versus unplanned simultaneous use would be linked to greater alcohol and cannabis consumption, but not to negative simultaneous use-related consequences.…”
Section: The Present Studymentioning
confidence: 86%
“…First, although our analyses were more ecologically valid than many, data were collected at the daily rather than momentary level. Although next-day retrospective reports of subjective response are subject to recall bias, several other studies have used daily dairies to test overall past-day subjective response (e.g., Fairlie et al, 2021;Linden-Carmichael et al, 2020;Lipperman-Kreda et al, 2017). Nonetheless, it was not possible in the current study to establish temporal precedence for drinking and subjective responses/craving and medication ingestion.…”
Section: Discussionmentioning
confidence: 87%